An interregional system dynamics model of animal disease control: Applications to foot-and-mouth disease in the Southern cone of South America - Rich, Karl M. (Wiley, 2008)
Foot-and-mouth disease (FMD) is costly for meat producers, given its ability to rapidly spread over space, with control efforts in one region crucially depending on the control efforts undertaken in other regions. This paper presents a model of FMD control that applies system dynamics to the spatial spread of disease among South American countries with traditionally different control regimes and assesses the impact of alternative control strategies. Model results demonstrate that preventative vaccination led to shorter outbreaks (by over 2 weeks) than other strategies, though the resources required to implement this may be difficult to mobilize. The model also shows that a combination of region-specific policies often controls disease better than uniform region-wide approaches, suggesting the need for improved multinational coordination of disease control.